(untitled) (Physical Education, Health and Social Sciences, 2025)
The major focus of this research to investigates the quality of education in public vs private sector universities in Pakistan. With the passage of the time and high demand in higher education, the number of universities increase in both sector, therefore it is the need of this era measure the quality of education of both sector. Quantitative research approach with positivist philosophical paradigm was used in descriptive nature of this research. Comparative research design with survey method was adopted for this study. The population of this study was all HEC recognized Universities which were located in Lahore district. Two stage sampling technique were used to select the sample in which criterion sampling technique was on first stage and the stratified random sampling was on second stage. Thus the total sample size of this study was six universities on equal proportion (3 public and 3 private) and 900 students were selected (per universities 150). Five factor was included to investigate the quality of education in which teaching efficacy, institutional facilities, curriculum, research opportunities and library services. Findings were revealed that there is a significantly difference between the Public vs private universities in Punjab. It is recommend that set the criteria of quality of education for both sector and need to establish a framework to meet the criteria.